Interactions between concerns for the environment and other sources of concern in 31 European countries. (1st January 2023) - Marasco, Addolorata; Romano, Alessandro; Sotis, Chiara
Abstract: Understanding how different sources of concern interact in people's mind is a question that has entertained generations of scholars. The finite-pool-of-worry (FPW) hypothesis states that humans have limited resources to worry, thus when they are worried about one issue they become less worried about other issues. Instead, the affect generalization theory (AGT) posits that an increased level of worry about one threat increases concerns about related threats. To this end, we adopt a Lotka–Volterra model to detect instances of AGT and FPW among worries for the environment, economy, safety, social issues and immigration in 31 European countries between 2012 and 2019 (Eurobarometer data). Consistently with AGT, we find that an increase in the concern for the environment often favors the growth of concerns for the economy. Meanwhile, consistently with FPW, an increase in the concerns for the economy and for other sources of worry, often pushes down concerns for the environment. Building on our results, we hypothesize the existence of a pyramid of worries. At the bottom of the pyramid lie worries like concerns for the economy, which generally predate other worries. Concerns for the environment lie at the very top of the pyramid as they are generally predated by other worries. Last, we find that AGT and FPW can coexist not only over time and across countries, but also as a result of an asymmetric interaction.